The human factor in learning design, research, policy, and practice - MacLean, Piers; Cahillane, Marie (Emerald, 2015)
Purpose – The purpose of this paper is to highlight the importance of coherent alignment of current theory from cognitive psychology with practice and policy in training and education institutions developing e-learning materials and present recommendations emphasising the human factor within processes. Design/methodology/approach – In this paper a recent empirical study which applies current theory from cognitive psychological and multimodal learning research provides the backdrop to discussion about alignment of strategic vision, through policy, to effective practice. Findings – Despite advances in cognitive psychology which can be applied to targeting effective and measurable training and education, many institutions fail to maintain updated e-learning strategy and policy resulting in a negative impact on practice and the learner experience. Practical implications – The model presented in this paper is intended to promote thoughtful discussion about the processes and framework necessary for improved collaboration and communication supported by ongoing evaluation of institutional e-learning policy such that policy becomes a dynamic process congruent with developments in the learning sciences. Social implications – The paper includes recommendations for a refined view of knowledge, skills, and attitudes and alignment of policy with practice and theory and will be of interest to training and education institutions seeking to review their policies for training needs analysis and e-learning. Originality/value – This paper offers an up-to-date view of training needs analysis and multimedia design for training discrete psychomotor skills. It will be of value to organisations and institutions providing training and education mediated by technology as well as those involved in the design of training interventions.
Keywords: Cognitive psychology; Human factors research; Multimodal learning; e-Learning